2023
DOI: 10.1007/s10900-023-01218-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Knowledge and Awareness of HCV Infection and Screening Test: A Cross-Sectional Survey Among an Italian Sample

Abstract: Addressing HCV represents a public health priority, especially in Italy, which has the highest HCV prevalence in Europe. This study primarily aimed to explore knowledge about the HCV infection and awareness of the existence of the HCV screening test in Italy, before the implementation of awareness campaigns in 2022. An online cross-sectional survey was conducted (December 2021–January 2022). The primary outcomes were: Disease Knowledge Score (DKS), Prevention and Transmission Knowledge Score (PTKS) (for both: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Fig. 4 Immunoreactivity of denatured and soluble recombinant proteins. The crude preparations of denatured core (4A: lane C, 4C: lane 1) showed immunogenic bands at M. wt.…”
Section: Assessment Of Specific Activity Of Soluble Recombinant Prote...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 4 Immunoreactivity of denatured and soluble recombinant proteins. The crude preparations of denatured core (4A: lane C, 4C: lane 1) showed immunogenic bands at M. wt.…”
Section: Assessment Of Specific Activity Of Soluble Recombinant Prote...mentioning
confidence: 99%
“…Still, the large number of currently ongoing infections worldwide estimated at 1.5 million new infections per year [ 3 ] besides the unavailability of prophylactic vaccine mandate prioritizing the preventive measures, particularly screening, at the same level as the treatment campaigns. Early diagnosis of HCV infection is not only advantageous for minimizing the risk of liver-related morbidity/mortality; it also serves to reduce the pool of infected persons and thereby restricts further transmission [ 4 ]. In general, HCV infection is primarily diagnosed by serological detection of anti-HCV antibodies (IgG) in serum samples, either by enzyme immunoassays (EIA) or chemiluminescence immunoassays (CIA) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…About one-third of the general population (31.2%) included in this study reported ever undergoing HCV testing, which was lower than that reported in high-income countries. In Italy, for example, 43.4% of the general population declared that it has undergone HCV testing in the past [ 30 ]. Moreover, this study found that 75.9% of the survey respondents who had undergone HCV testing did so during blood donation.…”
Section: Discussionmentioning
confidence: 99%